Statistical methods for the social & behavioural sciences a model-based approach - Flora, David B. (Thousand Oaks, California SAGE Publications, 2018)
Statistical Methods for the Social and Behavioural Sciences: A Model Based Approach is the essential guide for those looking to extend their understanding of the principles of statistics, and begin using the right statistical modeling method for their own data. It is particularly suited to second or advanced courses in statistical methods across the social and behavioural sciences.-- Provided by Publisher.
Foundations of statistical modeling demonstrated with simple regression -- Multiple regression with continuous predictors -- Regression with categorical predictors -- Interactions in multiple regression : models for moderation -- Using multiple regression to model mediation and other indirect effects -- Introduction to multilevel modeling -- Basic matrix algebra for statistical modeling -- Exploratory factor analysis -- Structural equation modeling I : Path analysis -- Structural equation modeling II : Latent variable models -- Growth curve modeling.
Includes bibliographical references (pages [437]-445) and index.
Keywords: Social sciences -- Statistical methods; Social sciences -- Statistics